If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 2) + -2(4 + -5x) = 5(x + 3) + -3 Reorder the terms: (2 + X) + -2(4 + -5x) = 5(x + 3) + -3 Remove parenthesis around (2 + X) 2 + X + -2(4 + -5x) = 5(x + 3) + -3 2 + X + (4 * -2 + -5x * -2) = 5(x + 3) + -3 2 + X + (-8 + 10x) = 5(x + 3) + -3 Reorder the terms: 2 + -8 + X + 10x = 5(x + 3) + -3 Combine like terms: 2 + -8 = -6 -6 + X + 10x = 5(x + 3) + -3 Reorder the terms: -6 + X + 10x = 5(3 + x) + -3 -6 + X + 10x = (3 * 5 + x * 5) + -3 -6 + X + 10x = (15 + 5x) + -3 Reorder the terms: -6 + X + 10x = 15 + -3 + 5x Combine like terms: 15 + -3 = 12 -6 + X + 10x = 12 + 5x Solving -6 + X + 10x = 12 + 5x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6' to each side of the equation. -6 + X + 6 + 10x = 12 + 6 + 5x Reorder the terms: -6 + 6 + X + 10x = 12 + 6 + 5x Combine like terms: -6 + 6 = 0 0 + X + 10x = 12 + 6 + 5x X + 10x = 12 + 6 + 5x Combine like terms: 12 + 6 = 18 X + 10x = 18 + 5x Add '-10x' to each side of the equation. X + 10x + -10x = 18 + 5x + -10x Combine like terms: 10x + -10x = 0 X + 0 = 18 + 5x + -10x X = 18 + 5x + -10x Combine like terms: 5x + -10x = -5x X = 18 + -5x Simplifying X = 18 + -5x
| 0.3x+9=39 | | (-11+n)/15=-1 | | 3xsquare+1=7x | | 2x+8(1-x)=20 | | 3x-70=44+9x | | 4y-10+y+28=5+6y+25-4y | | N-6/3 | | -81-4x=179+9x | | (-4i-10j+k)-(6i+10j+6k)=0 | | X+(2X)+(2X+5)=100 | | 7+3p-5=8p+6-3p | | 1/3y-3=5 | | 2y-8=-x | | -1=(v-2)/21 | | 14=.01875x^2+.1575x+1.5 | | (2n^2+1)= | | 5x+2-7x=6+2x | | -3x-149=85+10x | | x+(X*2)+(X*2+5)=100 | | 9x+3=27x | | 4=4x+3 | | (-2z^3/x)^3 | | 95-10x=45 | | (-9+a)/15=1 | | -102-2x=60+4x | | 12=-2/7v | | 7/8-1/6 | | 6y=3x+12 | | f(0)=0-0+1 | | 3x+3-6x=8+2x | | 10x-16x=48 | | -3x-4=29 |